KERJASAMA INDONESIA - TURKI DALAM BIDANG PERTAHANAN ALUTSISTA DARAT PEMBUATAN TANK MEDIUM PT PINDAD DAN FNSS TURKI PERIODE 2013-2017 - Fadhilah Hasyyati, - (2019)
This research is done due to complete writer's task and analyze Indonesian's lack in technology of defense industry. Up until now, Indonesia has gone better in developing it's defence. But to face the global world with all the danger of national and international threats, the growth is not enough to protect the nation. Indonesia's dependency of importing arms are still in a very high amount. One of Indonesian army's most needed arms are Medium Tanks and Light Tanks. But these types aren't much suitable in helping army's work. Leopard Tanks, which is classified as heavy tanks are too big and heavy to be operated in this country's field. Light tanks are not strong enough to deal with severe attacks. Turkey has all it takes to help fullfil what Indonesia needs. With it's ability to be independently build the technology of defence industry and based on a lot of factors that keep the relationship well-firmed, both countries decided to cooperate The cooperation between both countries was to build Medium Tank without forgetting to support both countries' national interests. In this international cooperation in defense industry, transfer of technology method were used. So in order to help Indonesia in growing it's technology and becoming independent at producing local arms, this international cooperation in defense industry was held through PT Pindad and FNSS Defence System in 2013-2017 period of time